(untitled) (Research, Society and Development, 2024)
The objective was to discuss the justifications for performing euthanasia for convenience, of domestic dogs and cats, according to normative and bioethical approaches. Euthanasia for convenience is that performed without the animal presenting a clinical condition that would justify such a procedure. Is the one that occurs due to financial issues, changes in personal circumstances, little time for the care of the animal, feeling of incapacity or unwillingness to take care of the animal. The increase in procedures that have been made available in veterinary medicine leads to the impasse of very high treatment costs. In Brazil, it must be considered that because there are, in the human area, expensive treatments financially supported by the Sistema Único de Saúde (SUS), or Health Insurance, the population is left without reference to the values of health procedures. The performance of euthanasia is a determinant contributor to the risk of suicide and psychological distress in veterinarians. It is noteworthy that culture and religion can significantly influence attitudes towards euthanasia and death. Therefore, whether from a value (ethics) or religious point of view, veterinarians and owners may not agree with the practice of euthanasia and this must be respected. The convenience euthanasia of dogs and cats is a topic for bioethics to address, as it involves interests and commitments inherent to the animal, the tutor/owner and the veterinarian. In Brazil, euthanasia for convenience is not normatively supported and, bioethically, it is little discussed.